WACANA TUKAR PERAN RUMAH TANGGA DALAM KANAL YOUTUBE WOMANTALK - Ningrat, Leny Wahyu; Abrian, Rizky (Universitas Pendidikan Ganesha, 2024)
The phenomenon of changing roles in the household often occurs today, where women are busy working, while men take care of the house. This condition can give rise to family conflict, because it is contrary to natural norms which should be, namely that the husband earns a living and the wife takes care of the house. However, even though quite a lot of people have experienced an exchange of roles in the household. This phenomenon is still considered taboo, especially by Indonesian society. Therefore, this research was conducted to explore the position of women seen from the perspective of the subject and object as well as when seen from the reader's position. Placed in the discourse on the video on the Womantalk YouTube channel entitled